Expression of Β-Endorphin In Relieving Inflammation Pain after Dry Cupping Therapy - Imam Subadi (Program Pendidikan Vokasi Universitas Brawijaya, 2014)
Pain is a chief complaint most frequently seen in daily practice. Dry cupping therapy has been used for pain management but the mechanism of action is unclear. Beta endorphin is an endogenous morphin that can relief pain.The objective of this study is to show the relationship betweenβ-endorphin expression and pain relief in dry cupping.This experimental study employed randomized control group post test design. Twenty four Wistar rats (Rattus norvegicus) were assigned to three groups of 8 subjects, which were normal rats (control negative), group undergoing Complete Freund’s Adjuvant (CFA) only (control positive group) and group undergoing CFA and dry cupping (negative pressure: - 200 mmHg, 5 minutes). Samples were retrieved from skin and performed immunohistochemical of monoclonal anti β-endorphin. Pain threshold reaction time was measured by hot-plate. Data were then statistically analysed by Independent-Sample t Test, Linear Regresion analysis using SPSS version 17.This study found out that expression of β-endorphin, p= 0.000 and pain threshold reaction time on dry cupping, p= 0.001 had increased compared with the control group. There was relation between increased β-endorphin with pain threshold reaction time in dry cupping (β= 0.542; p= 0.030). In other words, dry cupping can decrease pain caused by the expression of β-endorphin